RETRACTED: The Effect of Workload, Discipline, and Motivation on Employee Performance at Vania Hospital Bogor City - Felita Charity Wulandari; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aimed to determine and analyze the effect of workload, discipline, and work motivation on employee performance at Vania Hospital, Bogor City. The data collection was divided into two parts namely primary and secondary data where primary data was obtained by distributing questionnaires to 65 respondents. The data that has been collected was then analyzed by inferential analysis with multiple linear regression and hypothesis testing. As a result, there was an insignificant effect between workload (X1) and employee performance (Y), discipline (X2) has a positive and significant effect on employee performance (Y), motivation (X3) has a positive and significant effect on employee performance (Y).